A closer look at fertilizer legislations for silage maize across selected European countries: part II–overestimation of economically optimal nitrogen rates - Josephine Bukowiecki; Larissa Ullrich; Martin Komainda; Antje Herrmann; Kurt Möller; Frank Liebisch; Johannes Isselstein; Manfred Kayser; Michael Grunert; Henning Kage; Insa Kühling (Nutrient Cycling in Agroecosystems, 2026)
Silage maize cultivation in Central Europe offers significant potential for improving nitrogen (N) efficiency, but quantifying N savings under current fertilization regulations and identifying further opportunities for improvement remain crucial. This study addresses these gaps by analyzing the influence of site-specific and management factors on the economically optimal N fertilization rate (EONR). EONR was calculated for 223 yield response functions across diverse silage maize cultivation conditions using a quadratic-plateau function, which outperformed quadratic and linear-plateau models in describing maize yield response to increasing N rates. A linear regression model was developed through a multistage analysis, incorporating only significant parameters available at the start of the growing season to estimate EONR. These EONRs, along with representative silage maize cultivation scenarios, were used to evaluate N fertilization recommendations within national frameworks. Key influences included management practices affecting plant residue quantity and carbon-to-nitrogen ratios, along with weather and soil parameters. Optimal management for silage maize following grain cereals, the predominant pre-crop in many regions, involved straw removal and frost-killed non-legume winter cover crops to maximize N saving potential. Official N fertilization recommendations exceeded calculated EONRs on average by more than 14%, with minimal correlation (R 2 < 0.1). In contrast, the developed regression model estimated EONR with a R adj 2 of 0.30, highlighting key research areas and opportunities for improving N efficiency in silage maize cultivation in Central Europe.

Age and body mass index are associated with dorsolateral prefrontal cortex activation in response to unhealthy food cues - Floor van Meer; Laura N. van der Laan; Gabriele Eiben; Lauren Lissner; Maike Wolters; Stefan Rach; Manfred Herrmann; Peter Erhard; Denes Molnar; Gergely Orsi; Roger A.H. Adan; Paul A.M. Smeets (Appetite, 2025)

Agriculture intensity and landscape configuration influence the spatial use of wildcats across Europe - Héctor Ruiz-Villar; Matteo Luca Bastianelli; Marco Heurich; Stefano Anile; Francisco Díaz-Ruiz; Pablo Ferreras; Malte Götz; Mathias Herrmann; Saskia Jerosch; Fernando Jubete; José María López-Martín; Pedro Monterroso; et al. (Biological Conservation, 2023)

Large-scale genetic census of an elusive carnivore, the European wildcat (Felis s. silvestris) - Katharina Steyer; Robert H. S. Kraus; Thomas Mölich; Ole Anders; Berardino Cocchiararo; Christiane Frosch; Alexander Geib; Malte Götz; Mathias Herrmann; Karsten Hupe; Annette Kohnen; Matthias Krüger; et al. (Conservation Genetics, 2016)

Intertemporal choice behavior is constrained by brain structure in healthy participants and pathological gamblers - Bahram Mohammadi; Anke Hammer; Stephan F. Miedl; Daniel Wiswede; Josep Marco-Pallarés; Manfred Herrmann; Thomas F. Münte (Brain Structure and Function, 2016)

The neural basis of impulsive discounting in pathological gamblers - Stephan F. Miedl; Daniel Wiswede; Josep Marco-Pallarés; Zheng Ye; Thorsten Fehr; Manfred Herrmann; Thomas F. Münte (Brain Imaging and Behavior, 2015)

H-D exchange on graphite–potassium intercalation compounds - Siegbert Rummel; Michael Herrmann; Manfred Wahren; Safar M. Yunusov; Margarita A. Ilatovskaya; Yuri B. Isaev; N. D. Lapkina; Yuri N. Novikov; Vladimir B. Shur (Isotopes in Environmental and Health Studies, 2012)

Modification of caffeine effects on the affect-modulated startle by neuropeptide S receptor gene variation - Katharina Domschke; Benedikt Klauke; Bernward Winter; Agnes Gajewska; Martin J. Herrmann; Bodo Warrings; Andreas Mühlberger; Katherina Wosnitza; Andrea Dlugos; Swantje Naunin; Kathrin Nienhaus; Manfred Fobker; et al. (Psychopharmacology, 2012)

Erythropoietin: Novel Approaches to Neuroprotection in Human Brain Disease - Hannelore Ehrenreich; Carlotta Aust; Henning Krampe; Henriette Jahn; Sonja Jacob; Manfred Herrmann; Anna-Leena Sirén (Metabolic Brain Disease, 2004)

An experimental approach to Neolithic shifting cultivation - Manfred Rösch; Otto Ehrmann; Ludger Herrmann; Erhard Schulz; Arno Bogenrieder; Johann Peter Goldammer; Matthias Hall; Hans Page; Wolfram Schier (Vegetation History and Archaeobotany, 2002)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)